2020
DOI: 10.1002/ijop.12664
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the relationship between umbilical blood cord donation and the impact of social distance on altruism and trust

Abstract: A llogeneic umbilical cord blood (UCB) donation is a pro-social behaviour directed to strangers that has a certain cost for the donor. Although the promotion of such behaviour is an important goal for many countries' health systems, little is known about the reasons that would lead to it. With this study, we explored how the impact of social closeness on altruism and trust could be related to UCB donation in a sample of new-mothers (N = 167). Participants played hypothetical Dictator and Trust games with socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…In line with previous studies, we found that altruism was affected by social distance, with participants being more generous to close compared with distant ones [ 33 , 39 , 56 , 57 ]. In particular, participants donated the most generous amount of money to parents and siblings and the lowest amount of money to neighbours and strangers.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In line with previous studies, we found that altruism was affected by social distance, with participants being more generous to close compared with distant ones [ 33 , 39 , 56 , 57 ]. In particular, participants donated the most generous amount of money to parents and siblings and the lowest amount of money to neighbours and strangers.…”
Section: Discussionsupporting
confidence: 92%
“…While the lack of effect on social distancing behaviours might be due, again, to a ceiling effect due to the impossibility of ignoring those rules [ 53 , 54 , 55 ], the effect found on the hygiene behaviours supports the hypothesis that the prosocial attitude towards close ones and not the population in general determines the compliance to these rules. A lower impact of social distance on altruism (more generosity towards distant ones) has been found only in extraordinary altruists such as kidney donors [ 34 ], in mothers who decide to donate umbilical blood cord to strangers [ 39 ], and in older adults who might develop more self-transcendent goals [ 59 ]. In contrast, parochial altruism seems to emerge as a consequence of warfare and between-group competition to promote individual and child fitness [ 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation